Prognosis of Streptococcus pneumoniae endocarditis in France, a multicenter observational study (2000–2015). (1st August 2019) - Périer, Amandine; Puyade, Mathieu; Revest, Matthieu; Tattevin, Pierre; Bernard, Louis; Lemaignen, Adrien; Boutoille, David; Allal, Joseph; Roblot, France; Rammaert, Blandine
Abstract: Background: Streptococcus pneumoniae is responsible for <2% of infective endocarditis (IE). The aim of this study was to assess the prognosis of pneumococcal IE. Methods: This multicentric observational retrospective study included adult patients presenting with definite S. pneumoniae IE according to modified Dukes criteria from four French university hospitals over a 15-year period, January 2000–December 2015. Survival rate at 90 days and 2 years after diagnosis, appropriateness of antibiotherapy, and pneumococcal vaccination status were determined. Risk factors for mortality were studied by univariate analysis. Results: Of 3886 patients admitted with IE during the study period, 50 (1.3%) had pneumococcal IE, mostly males ( n  = 38, 76%), with a mean age of 60 ± 14 years. Predisposing conditions for IE or for invasive pneumococcal disease (IPD) involved 24% and 78% of the cases, respectively. Only 2 patients were vaccinated against pneumococcus before IE and 13 (26%) after IE. Antimicrobial strategy was in accordance with the 2015 ESC Guidelines in 28%. Cardiac surgery was performed in 56%, and was associated with better survival ( p  = 0.012). In the 40 patients followed until 2 years, the survival rate was 67%, deaths occurring mostly before 90 days. Age ≥ 65 was a risk factor for mortality ( p  = 0.011). Conclusion: Pneumococcal IE remains rare but with a poor prognosis. Resort to surgery is yet to be determined. Predisposing conditions for IPD are the main factors leading to pneumococcal IE. They could be prevented by vaccine coverage improvement. Highlights: Pneumococcal infective endocarditis (IE) accounted for 1.3% of definite IE. Mortality reaches 17% at 90 days. Having a predisposing condition to invasive pneumococcal disease is the leading cause of pneumococcal IE.